The Influence of Islamic Banks on Growth in Sumatra - Rustam, Dicky; Putri, Adinda Rianson (Rangkiang: Journal of Islamic Economics and Business, 2025)
Islamic banking plays a vital role in promoting inclusive and sustainable economic growth, particularly in regions with significant Muslim populations such as Sumatra. However, empirical evidence on how Islamic banking contributes to regional economic development remains limited. This study investigates the impact of Islamic banking on economic growth in ten provinces across Sumatra from 2019 to 2024. Using a panel data regression approach, the analysis focuses on three key variables of Islamic banking performance - assets, financing, and Third-Party Funds (TPF) - with economic growth represented by Gross Domestic Product (GDP). The results reveal that financing and TPF significantly and positively influence economic growth, while total assets have no significant effect. These findings highlight the importance of channeling Islamic banking funds effectively through financing activities to strengthen regional economic performance. The study contributes to the understanding of Islamic finance as a driver of economic development and provides insights for policymakers to enhance the role of Islamic banks in supporting regional growth